We are not all equal in the annals of science: European social sciences - Peset, Fernanda (Anuario ThinkEPI, 2008)
Visibility in the Web of Science databases differs between the hard sciences and the social sciences, and between scholarship in English and in other languages. Quantitative data for 2006 are offered for SCI, SSCI, and AHCI, along with the author´s observations. The Spanish Foundation for Science and Technology (FECYT) has developed suggestions to reduce the marginalization of the social sciences and Spanish liberal arts in citations.
Keywords: Science sociology; Web of Science; Thomson ISI; SSCI; AHCI; Science Citation Index; SCI; Visibility; Impact.